Deciphering the focuses and trends in skin regeneration research through bibliometric analyses - Zhou, Jian; Dong, Chen; Shu, Qiuju; Chen, Yang; Wang, Qing; Wang, Dandan; Ma, Ge (Frontiers in Medicine, 2022)
Increasing attention to skin regeneration has rapidly broadened research on the topic. However, no bibliometric analysis of the field’s research trends has yet been conducted. In response to this research gap, this study analyzed the publication patterns and progress of skin regeneration research worldwide using a bibliometric analysis of 1,471 papers comprising 1,227 (83.4%) original articles and 244 (16.6%) reviews sourced from a Web of Science search. Publication distribution was analyzed by country/region, institution, journal, and author. The frequency of keywords was assessed to prepare a bibliometric map of the development trends in skin regeneration research. China and the United States were the most productive countries in the field: China had the greatest number of publications at 433 (29.4%) and the United States had the highest H-index ranking (59 with 15,373 citations or 31.9%). Author keywords were classified into four clusters: stem cell, biomaterial, tissue engineering, and wound dressing. “Stem cells,” “chitosan,” “tissue engineering,” and “wound dressings” were the most frequent keywords in each cluster; therefore, they reflected the field’s current focus areas. “Immunomodulation,” “aloe vera,” “extracellular vesicles,” “injectable hydrogel,” and “three-dimensional (3D) bioprinting” were relatively new keywords, indicating that biomaterials for skin regeneration and 3D bioprinting are promising research hotspots in the field. Moreover, clinical studies on new dressings and techniques to accelerate skin regeneration deserve more attention. By uncovering current and future research hotspots, this analysis offers insights that may be useful for both new and experienced scholars striving to expand research and innovation in the field of skin regeneration.